Rude customers and service performance: roles of motivation and personality. Issue 1 (25th January 2022) - Yoon, David J.
ABSTRACT: On the basis of the self-determination theory, we develop and test an integrative framework that explains when and why customer incivility impairs employee service performance. Using multisource data collected through two waves in a shopping mall, we found that the strength of the mediated relationship between customer incivility and employee service performance (via employee intrinsic motivation) varied based on employee core-self evaluations; the negative indirect effect of customer incivility via intrinsic motivation on service performance was weaker for employees with high levels of core-self evaluations than for employees with low levels of core-self evaluations.